Interferon-Free Strategies with a Nucleoside/Nucleotide Analogue - Feld, Jordan J. (Seminars in Liver Disease, 2014)
A key to effective interferon- (IFN-) free therapy for hepatitis C virus (HCV) infection is a direct-acting antiviral (DAA) with a high barrier to resistance that can act as the backbone to any regimen. Ideally, this agent should also be active against all HCV genotypes, be well tolerated and have few drug interactions. Nucleoside/nucleotide analogues (NAs) that inhibit the function of the HCV RNA-dependent-RNA polymerase fit these requirements and thus hold promise as a cornerstone for new IFN-free regimens. To date, the issue with this class of agents has been toxicity. Numerous NAs in early clinical development have led to significant toxicity leading to their abandonment. However, sofosbuvir, a prodrug of a uridine NA, has moved through development with a clean-safety profile leading to its recent approval. When combined with ribavirin (RBV) alone, sofosbuvir is effective against genotype 2 and even genotype 3 if duration is extended. There are currently limited data with this combination in genotype 1; however, when sofosbuvir is combined with other DAAs of different classes, it is highly effective in almost all patients. To date, sofosbuvir has been studied with protease, NS5A, and nonnucleoside HCV polymerase inhibitors, including as part of a fixed-dose combination single tablet with the NS5A inhibitor ledipasvir, with very high rates of SVR with as little as 8 weeks of therapy. Combining two DAAs to sofosbuvir may shorten therapy even further. Because of the poor replicative fitness of the S282T sofosbuvir-resistant variant, resistance to sofosbuvir has not been a significant clinical issue in trials thus far. In addition to sofosbuvir, other NAs are in early-stage development. Provided unanticipated toxicity does not emerge, NAs are likely to play a major role as a backbone for future HCV therapy. The rationale for using this class of agents and the clinical data available to date are reviewed.
Keywords: hepatitis C virus; interferon; nucleoside inhibitors; direct-acting antivirals; sofosbuvir